2016
DOI: 10.5551/jat.30000
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Nutrients and Blood Pressure

Abstract: Adverse blood pressure (BP) is a major independent risk factor for epidemic cardiovascular diseases affecting almost one-quarter of the adult population worldwide. Dietary intake is a major determinant in the development and progression of high BP. Lifestyle modifications, including recommended dietary guidelines, are advocated by the American Society of Hypertension, the International Society of Hypertension, the Japanese Society of Hypertension, and many other organisations for treating all hypertensive peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
35
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 94 publications
7
35
1
2
Order By: Relevance
“…However, higher SFA and lower PUFA consumption have been associated with higher BP (9). A summary of the International Study of Macro/Micronutrients and Blood Pressure (INTERMAP) reported that total PUFA, linoleic acid (LA), total n-3 FA, and α-linolenic acid (ALA), were inversely associated with BP (10). Data from meta-analyses (11,12) and clinical trials (13,14) have indicated that n-3 PUFA supplementation dose-dependently reduces BP in hypertensive patients, but not in normotensive individuals.…”
Section: Introductionmentioning
confidence: 99%
“…However, higher SFA and lower PUFA consumption have been associated with higher BP (9). A summary of the International Study of Macro/Micronutrients and Blood Pressure (INTERMAP) reported that total PUFA, linoleic acid (LA), total n-3 FA, and α-linolenic acid (ALA), were inversely associated with BP (10). Data from meta-analyses (11,12) and clinical trials (13,14) have indicated that n-3 PUFA supplementation dose-dependently reduces BP in hypertensive patients, but not in normotensive individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Among those observational studies, much research has been undertaken on whether there exists a relationship between magnesium contribution through dietary food and different cardiovascular risk factors, diabetes and cardiovascular diseases [38]. Thus, some studies have reported inverse associations between dietary magnesium intake and body mass index (BMI) or obesity [39,40], blood pressure [40,41], total cholesterol/LDL-cholesterol concentrations [42], and fasting glucose or type-2 diabetes [41,43,44], but the overall consistency for some of these factors is still low. Regarding the incidence of cardiovascular diseases, some studies have reported that high magnesium intake is associated with a lower risk of stroke, heart failure and total cardiovascular events [45,46], but less agreement has been observed for other cardiovascular events [38,47].…”
Section: Introductionmentioning
confidence: 99%
“…It has been also shown that total levels of α-linolenic acid is inversely associated with BP. 46 Berry and Hirsch 47 have reported that a 1% increase in serum α-linolenic acid is associated with a decrease in 5 mm Hg in systolic, diastolic, and mean arterial pressures.…”
Section: Flaxseed Oil and Arterial Pressures In Humansmentioning
confidence: 99%